2014
DOI: 10.2147/ndt.s68273
|View full text |Cite
|
Sign up to set email alerts
|

Post hoc analyses of the impact of previous medication on the efficacy of lisdexamfetamine dimesylate in the treatment of attention-deficit/hyperactivity disorder in a randomized, controlled trial

Abstract: BackgroundFollowing the approval of lisdexamfetamine dimesylate (LDX) in several European countries for the treatment of attention-deficit/hyperactivity disorder (ADHD) in children and adolescents with an inadequate response to methylphenidate (MPH) treatment, the aim of the present analysis was to establish the response to LDX in subgroups of patients with different ADHD medication histories.MethodsThis was a post hoc subgroup analysis of data from a 7-week, European, double-blind, dose-optimized, Phase III s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…SPD489-325 (ClinicalTr ials.gov identif ier: NCT00763971) was a 7-week, double-blind, efficacy and safety study of LDX in children and adolescents (aged 6-17 years) with ADHD and an ADHD-RS-IV total score of at least 28, conducted in Europe (48 sites in 10 countries). Details of the study design, results and previous post hoc analyses have been published [10,15,[17][18][19][20][21].…”
Section: Study Designs and Populationsmentioning
confidence: 99%
“…SPD489-325 (ClinicalTr ials.gov identif ier: NCT00763971) was a 7-week, double-blind, efficacy and safety study of LDX in children and adolescents (aged 6-17 years) with ADHD and an ADHD-RS-IV total score of at least 28, conducted in Europe (48 sites in 10 countries). Details of the study design, results and previous post hoc analyses have been published [10,15,[17][18][19][20][21].…”
Section: Study Designs and Populationsmentioning
confidence: 99%
“…Besides, our results suggested that MPH is a good candidate, especially with regards to fatigue and the rate of withdrawal, which makes MPHas the routine therapy clinically. LDX is used for patients with ADHD who have an inadequate response to MPH ( 12 , 14 ). Although MPH releases quickly in vivo as a stimulant, it can be controlled by modification, which is documented as osmotic release oral system ( 37 , 41 , 51 , 83 ), leading to moderate side effects ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lisdexamfetamine dimesylate (LDX) is a stimulant, normally used as a monotherapy or supplement for psychostimulants in ADHD treatment ( 10 , 11 ). In general, LDX is employed as prodrug due to its fast absorption and hydroxylation, which leads to a gradual and long lasting release ( 12 14 ). Methylphenidate (MPH) is a psych stimulant and is considered as the first-line therapy ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Responder analyses are widely accepted in the field, although there is currently no consensus regarding the most appropriate response criteria; previous analyses of ADHD treatments have employed specified percentage reductions from baseline in ADHD-RS-IV total score, a CGI-I score of 1 or 2, or a combination of the two. 3 , 29 31 The use of different levels of response in the present study provides information at different levels of stringency. Response rates decreased with increasingly stringent definitions, as would be expected.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Finally, it should be noted that this study found a numerically but nominally statistically nonsignificant larger placebo response in the stimulant-naïve group than in the prior MPH group, supporting other research suggesting that previous MPH exposure may influence the placebo response. 17 , 29 Future research, therefore, should specifically address the question of whether prior exposure to MPH changes the outcome on subsequent pharmacological exposure.…”
Section: Limitationsmentioning
confidence: 99%